APLIKASI BEBERAPA DOSIS PUPUK FOSFOR UNTUK PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS SORGUM (Sorghum bicolor (l.) Moench) - Leonalarisa Sitepu; Elza Zuhry; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this study was to know the growth and yield of some varieties of sorghum which were given several dose phosphorus fertilizer.This research has been conducted in Field Experiment and the plant breeding laboratory, Faculty of Agriculture, University of Riau, from April 2014 to October 2014.The study,s arranged experimentally Randomized Block Design with two factors namely varieties of sorghum and phosphorus fertilizer with three block. First factor are Kawali, Numbu, Pahat dan Mandau. Second factor are SP-36 45 kg/ha, SP-36 90 kg/ha dan SP-36 135 kg/ha. Parameters observed were plant height, trunk base diameter, the number of leaves, number of segments per plant, flowering age, age of harvest, panicle lenght, weight seeds per panicle, weight 1000 seeds and yield per m2. Data were analyzed statistically using ANOVA and followed by Duncan’s New Multiple Range Test at level of 5%.The results showed that the provision of phosphorus fertilizer was significantly on various varieties who researched. The provision dose phosphorus fertilizer 90 kg/ha and 135 kg/ha significantly increase higher plants on varieties of Numbu. The different dose of phosphorus fertilizer 45 kg/ha and 90 kg/ha significantly increase the number of segments on varieties of Kawali and Numbu. The provision dose phosphorus fertilizer 45 kg/ha – 135 kg/ha significantly speed up the age of harvest on varieties of Pahat and Numbu. The provision dose phosphorus fertilizer 90 kg/ha has given highest yield/m2 on varieties of Pahat (8,5 ton/ha) and Mandau (8,7 ton/ha). The provision dose of phosphorus fertilizer 135 kg/ha given highest yield/m2 on varieties of Kawali (9,0 ton/ha). The increase dose phosphorus fertilizer 45 kg/ha – 90 kg/ha given highest yield on varieties of Pahat and Mandau, while increase dose phosphorus fertilizer until 135 kg/ha given highest yield on varieties of Kawali and Numbu. Keywords : Sorghum bicolor (l.) Moench, phosphorus fertilizer, yield component.